Effects Of Graphene Oxide Coating On The Properties Of Polyurethane/Nanofiller Nanocomposite Foams - Wing Foong, Chin (Universiti Sains Malaysia, 2022)
In this study, carbon black (CB) and multiwalled carbon nanotube (MWCNT) were used as fillers for the preparation of the polyurethane (PU) nanocomposite foams. The CB and MWCNT loadings were in the range of (1, 2.5, 5, 7.5 phr). Further, graphene oxide (GO) coating was applied on the surface of the PU/CB and PU/MWCNT nanocomposite foams to increase the electrical conductivity which is determined by the surface resistance. The properties of the PU nanocomposite foams were characterised using foam density measurement, scanning electron microscopy (SEM), and surface resistance tests. The foam density of the PU was increased as a result of the increasing loading of CB or MWCNT. Furthermore, the PU/MWCNT nanocomposite foam has a higher density than the PU/CB nanocomposite foam at the same nanofiller loading. The microstructure analysis of the PU nanocomposite foams found that the average cell size is reduced as the filler loading increases. This indicates that the CB and MWCNT can act as cell nucleation sites to promote cell growth. The surface resistance of PU/MWCNT nanocomposite foam is lower than that of PU/CB nanocomposite foams at the same filler loading. Interestingly, the surface resistance of PU nanocomposite foams (formulation PU-MWCNT-5wt%) decreases from 5.8 x 1010 Ω to 1.7 x 108 Ω by the GO coating. This indicates that the GO coating is capable of increasing the electrical conductivity of the PU nanocomposite foam. Overall, the PU nanocomposite foam with dissipative behaviour was successfully produced using a combination of filler (dispersed in the PU matrix) and GO coating method.